A catalytic asymmetric one-pot [3+2] cyclization/semipinacol rearrangement sequence: an efficient construction of a multi-substituted 3H-spiro[benzofuran-2, 1′-cyclopentane] skeleton. Issue 26 (13th March 2019) - Liu, Lin; Lei, Lin-Sheng; Zhan, Zong-Song; Liu, Si-Zhan; Wang, Yu-Xiao; Tu, Yong-Qiang; Zhang, Fu-Min; Zhang, Xiao-Ming; Ma, Ai-Jun; Wang, Shao-Hua
Abstract : We report an asymmetric construction of multi-substituted 3 H -spiro[benzofuran-2, 1'-cyclopentane]s with three new stereocenters and two new ring systems. Abstract : A facile and efficient method to form a chiral multi-substituted 3 H -spiro[benzofuran-2, 1′-cyclopentane] structural unit has been developed via a one-pot [3+2] cyclization/semipinacol rearrangement cascade. A catalysis system of Cu(ii )/BOX has been used to efficiently construct a key stereogenic center via a cyclization between substituted benzoquinones and allylic alcohols affording the desired products in good yields and with excellent enantioselectivities and diastereoselectivities (21 examples; up to 67% yields; up to 92% ee and up to >20 : 1 dr). This method provides an alternative strategy for the synthesis of the corresponding bioactive molecules containing spiro[benzofurancyclopentane] skeleton units.